(untitled) (Archaeologia Adriatica, 2010)
The archaeological site of Jalkovec − Police was discovered during construction along the route of the southwestern bypass for the city of Varaždin. Most of the finds were from the late Bronze Age, with some sporadic Roman finds. One damaged pit dated to the Middle Ages was also discovered. Police is the toponym for a gently elevated river bar located north of the Plitvica Stream and south of the Drava River. As throughout history this area was flooded and marshy, the settlements were usually located on similar slightly elevated positions. The partly excavated pit K 12 contained numerous pottery fragments, burnt animal bones, tiny pieces of charcoal, large river pebbles, a piece of iron slag, and a chipped piece of flint. Through C14 analysis, the pit was dated to 1111+54 cal AD. Through the analysis of the typological characteristics of the pottery fragments, the fill of the pit could truly be dated to the 11th-12th century transition, confirming the C14 dating. A considerable presence could be noted of decoration with a toothed wheel, which otherwise appears in the period from the 10th-14th centuries. The pottery production from this period is relatively unknown in Croatia, so the analysis of this pit is offered as a contribution to further research into the beginning of the High Middle Ages in northern Croatia.